Information and Communication Technologies in the Professional Development of Vocational School Teachers - Кristinka Č. Ovesni; Jelena J. Stanojević; Vera Ž. Radović (University of Belgrade, Teacher Education Faculty, 2019)
The paper elaborates on the professional development of the vocational school teachers by using the information and communication technologies. It describes a qualitative research which included 20 teachers of vocational schools in the territory of the Republic of Serbia. The main aim of the research was to explore the vocational teachers' professional development which involves using the information and communication technologies and to provide answers to the following questions: To what extent are the vocational school teachers prepared in terms of their education for using the information and communication technologies in their professional development? What are the opinions of these teachers regarding the use of the information and communication technologies in their professional development? What are the forms of using these technologies in the vocational school teachers' professional development? The research findings indicate that there are several types of teachers' narratives regarding the above-mentioned questions and that these types vary relative to teachers' years of work experience. All teachers expressed positive attitudes towards using the information and communication technologies in their professional development. They have been trained to use these technologies, but the scope and intensity, as well as the preferred forms, of using these technologies for the purpose of professional development vary among the teachers.